USING SMOOTHNESS-CONSTRAINT LEAST-SQUARES INVERSION OF SCHLUMBERGER CONFIGURATION RESISTIVITY GEOELECTRIC METHOD TO ANALYZE GROUNDWATER DISTRIBUTION AT PADANG SELATAN (EINSTEIN (e-Journal), 2025)
This research aims to analyze the distribution of groundwater in the South Padang area through the application of the Smoothness-Constraint Least-Squares Inversion (SCLSI) method to the Schlumberger configuration geoelectric data. This method was chosen because of its ability to produce a smoother and more accurate resistivity model, and to overcome noise problems in geoelectric data. Measurements were taken at several points with the Schlumberger configuration, which were then processed using SCLSI to map the soil layers and the presence of groundwater. The analysis results showed significant resistivity variations, where areas with low resistivity were identified as potential groundwater accumulation zones. This study makes an important contribution to water resources management, especially in determining the location of exploration and sustainable groundwater management. The results of this study are expected to serve as a reference for the development of groundwater management policies in the area.